Effet des facteurs environnementaux sur la structuration de la flore ligneuse du Karthala (Grande-Comore, Océan indien) - Charahabil Mohamed Mahamoud; Léonard Elie Akpo (VertigO)
Understanding how environmental factors determine the distribution of plant and / or animal species is at the heart of the questions tackled in ecology and biogeography, particularly in islands where biodiversity is often original and the environnemental conditions unique. In this study, a relation between the spatial distribution of species and environmental factors is established. The ecological niche modeling of the most frequent species (relative frequency greater than 5%) of the Karthala forest was carried out using the software Maxent 3.2 (Maximum entropy). The relative contributions of the environmental factors used in the model were used to establish clusters of species with the same environmental requirements using ascending hierarchical classification (AHC). The relationship between species structure and environmental factors is determined using a co-inertia analysis applied to two tables (species / environmental factors and species / sites) and resulted in the identification of species’ clusters present in the same habitats and having the same climatic requirements. This co-structure analysis showed that the structure of the species is explained by the environment and more specifically by the rainfall and the slope. The temperature has a very limited influence on the structuration of the flora. Thus it’s demonstrated that the ecological niche approach combined with classical multivariate analysis is an approach suited for the identification of the environmental factors influencing the distribution of the phytodiversity of a forest. The results of this study should be used to better guide the management and conservation programs of the wooded areas of the Comoros archipelago. For a better understanding of the habitat pattern and the organization of the vegetation it will be interesting to consider in further studies the soil and anthropogenic effects.